The effects of prolonged stress exposure on the brain of rats and insights to understand the impact of work-related stress on caregivers - Pujo, Jean Marc; Fitriani, Dewi Yunia; Ben Saad, Hajer; Ghariani, Marwa; Dghim, Amel; Mellouli, Manel; Burin, Antoine; Mutricy, Remi; Houcke, Stephanie; Roujansky, Ariane; Mansyur, Muchtaruddin; Nkontcho, Flaubert; et al. (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Stress exposure is a significant concern in the healthcare sector. This animal model study aims to reproduce caregivers' working conditions and determine their impact on the brain.Method: Twenty-four healthy male rats of the Wistar strain were divided into four groups.Three groups were submitted each to one stressor for 21 days, while the fourth group was used as a control. Stressors were food and water deprivation (FW), permanent illumination (PI), and forced swimming (FS). At the end of the experiment, rats were euthanized, and stress biomarkers, biological parameters, and DNA damage were measured.Results: Prooxidant biomarkers rates raised in the different groups (+50 to +75%) compared to the control (p<0.0001). Urinary corticosterone rates increased in all stressed animals, mainly in the PI group, with changes of up to +50% compared to controls. Acetylcholinesterase levels decreased to -50% (p<0.0001 for the three exposed groups). Total ATPase, (Na + /K + )-ATPase, and Mg 2+ -ATPase activities decreased in all stressed groups. The percentage of brain cell congestion and apoptosis was 3% for the FW group (p<0.0001), 2% for the PI group (p<0.0001), and 4% for the FS group (p<0.0001) compared to the control (0.8%). DNA damage was observed in all exposed groups. Finally, we noticed behavioral changes and depressionlike syndrome in all stressed rats.Stressful conditions like the working environment in caregivers can trigger several pathophysiological processes leading to oxidative, neurochemical stress, and hypothalamic-pituitary-adrenal disorders. These changes can progress to cell damage and apoptosis in the brain and trigger psychological and physical disorders.